2016
DOI: 10.1097/igc.0000000000000607
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TOP2A as a Predictive Marker for Endometrial Cancer With Taxane-Containing Adjuvant Chemotherapy

Abstract: Patients with TOP2A overexpression have a worse prognosis compared with those with TOP2A nonexpression, and TOP2A may be a useful biomarker in patients receiving adjuvant taxane-platinum regimens with moderate- to high-risk endometrial cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…Moreover, TOP2A may be used as a biomarker in patients receiving adjuvant taxane-platinum regimens with moderate-to high-risk EC (3). The previous study (3) coincides with the present result that TOP2A was significantly upregulated in EC of G3 compared with EC of G1. In 2018, Pei et al (16) reported that the upregulation of TOP2A was observed in pancreatic cancer compared with non-tumor tissues, and significantly correlated with tumor metastasis and shorter survival.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, TOP2A may be used as a biomarker in patients receiving adjuvant taxane-platinum regimens with moderate-to high-risk EC (3). The previous study (3) coincides with the present result that TOP2A was significantly upregulated in EC of G3 compared with EC of G1. In 2018, Pei et al (16) reported that the upregulation of TOP2A was observed in pancreatic cancer compared with non-tumor tissues, and significantly correlated with tumor metastasis and shorter survival.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, TOP2A serves a principal role in controlling the cell cycle and maintaining the integrity of the genome. It was reported that TOP2A was upregulated in numerous cancer types, including endometrial cancer (3,4,15), pancreatic cancer (16), prostate cancer (17) and breast cancer (18). In agreement with the present results, the increased TOP2A expression level indicated an association with more aggressive tumor behavior, including myometrial infiltration, and was associated with the prognosis in patients with EC (4,15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to IPI score, these prognostic models also did not include tumor-specific biological factors, and can therefore not be used for targeted therapies (31,34). nm23, TOP2A, MUM-1 and VEGF are very common markers used to estimate the progression, infiltration and metastasis ability of many malignant tumors, particularly carcinomas (14,(40)(41)(42)(43)(44). Although their prognostic role in various carcinomas has been widely investigated over time, such as breast (45), pancreatic (12) and renal cell carcinoma (42), to the best of our knowledge, a limited number of have focused on their value in lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear DNA topoisomerase 2-α (TOP2A) is an essential enzyme required for DNA replication and transcription, as it controls and alters the topological states of DNA (12). The overexpression of TOP2A in carcinomas has been shown to be a reliable proliferation marker and to suggest poor prognosis (12)(13)(14)(15). The same results were confirmed in mantle cell lymphoma (16), with shorter survival in patients with higher TOP2A.…”
Section: Introductionmentioning
confidence: 88%